Down Syndrome and Information Science: an essential connection (Seminário Internacional de Informação, Tecnologia e Inovação, 2025)
This study investigates the dynamics of information seeking and use by caregivers of children with Down syndrome, a genetic condition that requires multidisciplinary intervention. The research highlights the need for public authorities to disseminate information about the syndrome. To this end, a bibliometric analysis was conducted using the Brapci database, which focuses on Information Science. Preliminary results indicate that there is limited discussion on the topic within the database, revealing the need for reliable and accessible information sources in this field. The research is still in progress but suggests the creation and implementation of policies to promote knowledge dissemination about the syndrome within the field of Information Science.